2021
DOI: 10.37213/cjal.2021.31382
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Task Repetition on Child EFL Learners’ Oral Performance

Abstract: While the role of task repetition has received much attention in task-based research, few studies have examined how exact task repetition affects the performance of child second language learners. Also, little is known about the impact of exact task repetition on trade-off effects between linguistic performance areas among child learners. To help fill this gap, we investigated the impact of task repetition on 40 Chinese EFL learners’ oral production. The children repeated the same story-telling task three time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…The findings are in agreement with Spring (2020), who found that video project-based learning could enhance students' speaking proficiency in terms of fluency and accuracy but did not make gains in complexity, especially lexical work. A study conducted by Révész and Sun (2021) also revealed that tasks on oral productions promoted students' linguistic fluency and accuracy but not complexity. It seems that students needed more time and courage to improve their linguistic complexity.…”
Section: Finding and Discussionmentioning
confidence: 98%
“…The findings are in agreement with Spring (2020), who found that video project-based learning could enhance students' speaking proficiency in terms of fluency and accuracy but did not make gains in complexity, especially lexical work. A study conducted by Révész and Sun (2021) also revealed that tasks on oral productions promoted students' linguistic fluency and accuracy but not complexity. It seems that students needed more time and courage to improve their linguistic complexity.…”
Section: Finding and Discussionmentioning
confidence: 98%
“…Penelitian sebelumnya membuktikan bahwa metode active recall dapat membantu siswa mengingat kosa kata bahasa Inggris baik melalui kuis dalam berbagai media, maupun tes beruntun (Alghamdi & Elyas, 2020;Katemba & Sinuhaji, 2021). Penelitian lain juga membuktikan selain sebagai sarana mengingat kosa kata metode active recall dapat membantu siswa dalam keakuratan pelafalan kosa kata Bahasa Inggris ( (Sun & Révész, 2021). Dalam pembelajaran sains, active recall terbukti dapat meningkatkan pemahaman siswa melalui teknik membuat mind map setelah mendapatkan materi pembelajaran, hal tersebut terjadi karena otak terus-menerus mengingat informasi dan hanya fokus kepada informasi penting (Karpicke & Blunt, 2011).…”
Section: Pendahuluanunclassified
“…One such issue is the spacing between task repetitions. A range of temporal gaps between task performances has been used in the literature, from immediate task repetition (e.g., Sun & Révész, 2021) to days (e.g., Gass et al., 1999) or weeks (e.g., Bygate, 2001). These gaps often appear to have been chosen arbitrarily (DeKeyser, 2018).…”
Section: Task Repetitionmentioning
confidence: 99%